The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.nicl.2021.102611
|View full text |Cite
|
Sign up to set email alerts
|

Tourette syndrome as a motor disorder revisited – Evidence from action coding

Abstract: Highlights Feature Binding/integration in the motor domain in Tourette Syndrome (TS) is examined. Motor binding processes and interleaved action are intact in TS. Binding processes are differentially modulated in the motor domain and sensori-motor processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 76 publications
(47 reference statements)
2
9
0
Order By: Relevance
“…Thus, in contrast to healthy controls, in whom stimulus–response translation processes reflected by C‐cluster modulations mediate binding on a behavioral level, 38,56 the motor component of perception–action integration processing is accentuated in FMD. The latter finding does not contradict the conceptualization of altered perception–action integration in FMD because both sensory and motor processes (R‐cluster) 57,58 constitute processes occurring in an event file 23 . R‐cluster effects were associated with activation differences in the inferior frontal gyrus, that is, BA44, a hub region of inhibitory control processes to implement executive control, 59,60 which have been shown to be altered in FMD 61 …”
Section: Discussionmentioning
confidence: 81%
“…Thus, in contrast to healthy controls, in whom stimulus–response translation processes reflected by C‐cluster modulations mediate binding on a behavioral level, 38,56 the motor component of perception–action integration processing is accentuated in FMD. The latter finding does not contradict the conceptualization of altered perception–action integration in FMD because both sensory and motor processes (R‐cluster) 57,58 constitute processes occurring in an event file 23 . R‐cluster effects were associated with activation differences in the inferior frontal gyrus, that is, BA44, a hub region of inhibitory control processes to implement executive control, 59,60 which have been shown to be altered in FMD 61 …”
Section: Discussionmentioning
confidence: 81%
“…An EEG study of lateral readiness potentials, a measure of activation and preparation of responses occurring in motor cortical areas, showed that action integration per se was normal in patients with TS, suggesting that TS is not only a movement disorder. 53 EEG studies characterizing oscillatory activity and functional connectivity revealed that children with tics exhibited abnormal activation and communication patterns within the frontal-parietal lobe network during cognitive inhibition 54 and that children with TS suppressed tics through a distributed brain circuit of cortical regions. 29 In an EEG study of TS patients and controls, movement-related EEG (i.e., mu- and beta-band oscillations) was examined just before voluntary movements and tics were performed.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its particularly notable motor symptoms, GTS has long been viewed and classified as a movement disorder, and treatment efficacy is indeed usually evaluated in terms of scores focusing on motor output [ 23 ]. However, several lines of research reviewed elsewhere [ 24 , 25 , 26 , 27 ] have reported numerous non-motoric peculiarities of GTS patients, such as hypersensitivity to external stimuli [ 27 ] and general perceptual processing [ 28 ], abnormal sensorimotor interaction [ 29 , 30 ], and a dependence of symptoms on attention [ 31 , 32 , 33 ]. Moreover, the degree to which motor symptoms can be controlled [ 34 ] has been reported to form the basis of cognitive–behavioral interventions, and an increased tendency to create habits has been observed [ 35 , 36 , 37 ].…”
Section: Quo Vadis?mentioning
confidence: 99%